The Knowledge Building International Project (KBIP): Scaling Up Professional Development Using Collaborative Technology - Laferrière, Thérèse; Allaire, Stéphane; Breuleux, Alain; Hamel, Christine; Law, Nancy; Montané, Mireia; Hernandez, Oscar; Turcotte, Sandrine; Scardamalia, Marlene (Scaling Educational Innovations, 2015)
Classroom-based knowledge building requires advanced pedagogies and collaborative technologies. It qualifies as disruptive innovation: progressively more impressive accounts of what students and teachers can accomplish alter beliefs regarding developmental, demographic, and cultural barriers. To establish knowledge-building communities requires effort from within as well as from outside the classroom. The Knowledge Building International Project (KBIP) has been rooted in school-university-government (SUNG) partnerships, along with their locally based networks of innovation. The chapter starts with a conceptualization of professional development in the digital era, and the main constituents of the Remote Networked School (RNS) initiative are presented. Next, a description of the SUNG partnerships follows. Emphasis is on agency, as it was observed in the RNS and in the SUNG dynamics of partnerships for classroom-based knowledge building: knowledge building as a shared vision, symmetric knowledge advancement, and multilevel, research-based innovation. Following is a descriptive analysis of the Knowledge Building International Project (KBIP 2007–2014) using Engeström’s (1987) third-generation activity theory framework (Engeström and Sannino 2010). Referring to Engeström’s expansive learning cycle (1987), further analysis is provided regarding the overcoming of double binds for KBIP expansion as an activity.